Perceptions of disputants on the role of coaching to enhance workplace mediation in South Africa - Gilbert, Charles (My University, 2020)
The practice of conflict coaching has emerged in countries outside of SA, with a body of knowledge growing on the application of coaching to mediation. Yet in SA there appears to be limited application of coaching to mediation. The research purpose was to determine disputants’ perceptions of challenges experienced in the mediation of one-to-one disputes between professionals, and after exposure to coaching, to gain their perceptions on the potential role of coaching in enhancing workplace mediation in South Africa – towards developing guidelines on how coaching could be adopted in the mediation process. The study adopted a qualitative research approach, with data collection conducted through two sets of face-to-face semi-structured interviews with seven disputants (with fourteen interviews conducted) in a university, by an independent interviewer. The coaching of the disputants was facilitated by the researcher after the first set of interviews, and before the second set of interviews. The disputants were assigned codes by the interviewer, and after transcription of the interviews, the transcripts were submitted to the researcher for thematic analysis. While most disputants perceived their mediation processes to be effective, all of them had experienced certain challenges in the pre-mediation phase, during the actual mediation itself and/or post-mediation. After receiving coaching as part of the study, the disputants all acknowledged that there were benefits of coaching. Their positive experience of coaching therefore assisted them to articulate how coaching could play a role in the pre-mediation and post-mediation phases. In pre-mediation, coaching could assist with the proactive de-escalation of the conflict experienced among the two disputants and with the preparation of the disputants for the mediation process. In the post-mediation phase, coaching could be used to facilitate closure in relation to the emotional aftermath, and follow-up with implementation of aspects of the mediation agreement. Furthermore, guidelines are recommended to key stakeholders on how coaching could be adopted within the mediation process.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2020
Keywords: Workplace conflict; Workplace disputes; Coaching; Conflict coaching; Mediation; Mediation process; SDG-8: Decent work and economic growth